2015
DOI: 10.1038/ejhg.2014.277
|View full text |Cite
|
Sign up to set email alerts
|

Primary coenzyme Q10 deficiency presenting as fatal neonatal multiorgan failure

Abstract: Coenzyme Q10 deficiency is a clinically and genetically heterogeneous disorder, with manifestations that may range from fatal neonatal multisystem failure, to adult-onset encephalopathy. We report a patient who presented at birth with severe lactic acidosis, proteinuria, dicarboxylic aciduria, and hepatic insufficiency. She also had dilation of left ventricle on echocardiography. Her neurological condition rapidly worsened and despite aggressive care she died at 23 h of life. Muscle histology displayed lipid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 20 publications
1
47
0
Order By: Relevance
“…Primary CoQ deficiencies—genetic diseases due to mutations in genes encoding CoQ biosynthesis proteins—are known to be caused by nuclear DNA mutations in COQ2 [145148], COQ4 [149, 150], COQ6 [151, 152], COQ7 [153], COQ8A ( ADCK3 ) [136, 154158], COQ8B ( ADCK4 ) [118, 159], COQ9 [160, 161], PDSS1 [162], or PDSS2 [163, 164] (Figure IA). These diseases variably disrupt multiple organ systems.…”
Section: Functions Of Coenzyme Q and An Overview Of Its Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Primary CoQ deficiencies—genetic diseases due to mutations in genes encoding CoQ biosynthesis proteins—are known to be caused by nuclear DNA mutations in COQ2 [145148], COQ4 [149, 150], COQ6 [151, 152], COQ7 [153], COQ8A ( ADCK3 ) [136, 154158], COQ8B ( ADCK4 ) [118, 159], COQ9 [160, 161], PDSS1 [162], or PDSS2 [163, 164] (Figure IA). These diseases variably disrupt multiple organ systems.…”
Section: Functions Of Coenzyme Q and An Overview Of Its Biosynthesismentioning
confidence: 99%
“…Therapy should be initiated as soon as possible to limit irreversible tissue damage [173]. The urgency is such that prior to diagnostic tests, newborn siblings of affected individuals have been treated [148]. …”
Section: Functions Of Coenzyme Q and An Overview Of Its Biosynthesismentioning
confidence: 99%
“…Renal symptoms are rarely isolated and commonly form part of a multisystemic disorder. Exceptions include some mtDNA mutations and some cases of CoQ 10 deficiency in which renal dysfunction might be the only clinical manifestation at presentation 24 . In general, the coexistence of neuromuscular symptoms and renal defects should raise suspicion of a mitochondrial defect 25 .…”
Section: Clinical Features Of Mitochondrial Diseasesmentioning
confidence: 99%
“…37 In order to exploit the "window of opportunity" whereby organ dysfunction may be amenable to CoQ 10 treatment, supplementation at birth has been suggested for siblings of CoQ 10 -deficient patients. 38 In vitro studies have indicated that the use of modified precursors of the quinone ring of CoQ 10 to bypass the enzymatic defect may be effective in treating specific mutations of the COQ6 and COQ7 genes. 39 Studies in yeast harboring the mutant COQ6 gene revealed that treatment with vanillic acid as well as 3-4-hydroxybenzoic acid could restore respiratory growth.…”
Section: Treatment Of Primary Coq 10 Deficiencymentioning
confidence: 99%